"I think it fits in": using process drama to promote agentic writing with primary school children. (25th March 2018) - Dobson, Tom; Stephenson, Lisa
Abstract: Set against the backdrop of children being 'alienated' from their writing, this paper is taken from a United Kingdom Literacy Association sponsored project where primary school teachers were trained to use process drama in order to give children more agency in their writing across the curriculum. Here, we use discourse analysis to think about the children's historical creative writing in relation to the drama lessons which are differently framed by the teachers. Building upon a theoretical model of process drama as involving 'embodied experience' and writing as problem‐solving, a case is made that process drama can lead to what we term 'agentic writing'. Agentic writing, we demonstrate, involves children actively translating their embodied experience of process drama into writing by making a range of intertextual borrowings. These borrowings serve both to capture and transform their embodied experience as the children gain agency by standing outside language to achieve 'double voicedness' and in doing so write sophisticated texts. Seeing the relationship between process drama and writing in this light, we argue, provides a means of reconnecting children to the act of writing.